Monitoring and pedagogical control in the European system of education - Yaroshchuk, L. H.; Vaseiko, Yuliia S. (Класичний приватний університет., 2021)
The article discusses the international research of educational quality in the countries of the European Union at the present stage. As an example of monitoring at international level there can serve the implementation of the international programs (TIMSS, PISA, PIRLS, CIVIC, LINGVA etc.) carried out with the support of International Association for the Evaluation of Educational Achievements (IEA) and Organization for Economic Cooperation and Development (OECD). There have been brighten up the variables affecting the results of the tests of those being tested. The international comparative researches provide identifications with not only positive aspects but also shortcomings of educational programs. Besides, on the basis of their results (information) the central educational bodies can apply tools which promote raising achievement of pupils, productivity of activity of teachers and overall performance of school institutions in general. At the same time, according to the international monitoring, it is possible to track the development of education in any country if the management of educational systems is decentralized.The authors prove that the latest developments in the field of monitoring are among the countries that make extensive use of France, Greece, Italy, Switzerland, Great Britain, the Netherlands, Denmark, Germany, etc. belong to the countries which widely use the last achievements in the sphere of monitoring, they have developed the classical theory of tests, then provided IRT and the based practice of testing for millions of pupils, organized the companies and services which develop tests, organize mass testing, are constantly engaged in collection of information for monitoring of quality of education. Experience of the western countries shows that they are ahead of us on scales of application of tests, the number of publications, preparation of scientific resources, level and quality of the theory of test techniques and control, modern technical means which are used in testing. Monitoring of school progress which took stable positions in the educational systems of the developed countries for the last decades gives an opportunity to obtain data on a condition of an educational system in the country. According to scientists not too many countries have accurate information on the level of knowledge of pupils. France, Great Britain are interested not only in the results of knowledge of pupils but also process of assimilation of knowledge and how to help pupils who have difficulties at school. Confirmation of the importance of this problem is an introduction in the European countries, in particular in Great Britain and France, of special training for teachers in estimation of knowledge of pupils – a course of a new discipline in higher educational institutions.
Keywords: international comparative studies; quality of education; educational systems; testology (testing appraisal); study results; monitoring; 371.26